2013
DOI: 10.1134/s0362119712060047
|View full text |Cite
|
Sign up to set email alerts
|

Eye movements in the process of reading as an indicator of development of reading skill

Abstract: The parameters of oculomotor activity were investigated using the video recording method when texts of different complexity were read by pupils with various reading skill levels. The parameters of eye move ments and their determination have been described. It has been shown that the total reading time, the average duration of fixations, and the total number of regressions decrease, and the amplitude of progressive and regressive saccades increases as the reading skill is formed, which testifies to the perfecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
1
4
0
1
Order By: Relevance
“…In the control group, in addition to correlations with other indicators of fixation number, we also observed that gaze fixation stability is directly correlated with amplitude of progressive saccades when reading. This correlation confirms previous results [ 35 , 36 ] associating more developed oculomotor reactions with more skilled reading.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the control group, in addition to correlations with other indicators of fixation number, we also observed that gaze fixation stability is directly correlated with amplitude of progressive saccades when reading. This correlation confirms previous results [ 35 , 36 ] associating more developed oculomotor reactions with more skilled reading.…”
Section: Discussionsupporting
confidence: 92%
“…We also correlated the age of participants to the reading parameters and found a clear dependence on age (except CV of progressive saccades) in the control group, while there was no correlation in the cerebellar group ( Table 3 ). The improvement of reading skills with age has been reported in numerous studies [ 35 , 36 , 46 ]. On one hand, saccadic cortical areas (frontal and parietal cortex) are less active in young children than in adolescents and adults [ 47 ], pointing to maturation of these areas with age.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…For Russian, several studies using eye tracking while reading have already been conducted, but they explored specific theoretical issues in low-level eye movements or sentence processing Anisimov, Fedorova, & Latanov, 2014;Bezrukikh & Ivanov, 2012;Chernova, 2015;Jouravlev & Jared, 2018). They aimed to answer questions unrelated to particular properties of the Cyrillic alphabet or reading strategies in Russian.…”
Section: Other Eye Movement Corpora Based On the Psc Protocolmentioning
confidence: 99%
“…Продолжительность фиксаций между саккадами отражает процессы интеграции и анализа входящей информации (Иванов и др., 2010;Bezrukikh, Ivanov, 2013;Frey et al, 2013;Rayner, Reingold, 2015;Rucci, Poletti, 2015;Lopez-Perez et al, 2016). Во время фиксации происходит смещение внимания, селекция места следующей фиксации и запоминание выбранной локации, принимается решение о генерации коррекционной или регрессивной (возвратной) саккады (Leigh, Zee, 2015).…”
unclassified